Postnatal experiences influence how the brain integrates information from different senses - Stein, Barry E.; Perrault Jr., Thomas J.; Stanford, Terrence R.; Rowland, Benjamin A. (Frontiers in Integrative Neuroscience, 2009)
Sensory processing disorder (SPD) is characterized by anomalous reactions to, and integration of, sensory cues. Although the underlying etiology of SPD is unknown, one brain region likely to reflect these sensory and behavioral anomalies is the superior colliculus (SC), a structure involved in the synthesis of information from multiple sensory modalities and the control of overt orientation responses. In the present review we describe normal functional properties of this structure, the manner in which its individual neurons integrate cues from different senses, and the overt SC-mediated behaviors that are believed to manifest this “multisensory integration.” Of particular interest here is how SC neurons develop their capacity to engage in multisensory integration during early postnatal life as a consequence of early sensory experience, and the intimate communication between cortex and the midbrain that makes this developmental process possible.